Spheroids of HER2-Positive Breast Adenocarcinoma for Studying Anticancer Immunotoxins In Vitro; Acta Naturae; Vol. 9, №1 (32) - Balalaeva I. V. Irina Vladimirovna; Sokolova E. A. Evgeniya Anatoljevna; Puzhikhina A. D. Alena Dmitrievna; Brilkina A. A. Anna Aleksandrovna; Deev S. M. Sergey Mikhaylovich (2017, 2017)
Title screen